Next-generation of selective histone deacetylase inhibitors. Issue 34 (24th June 2019) - Yang, Feifei; Zhao, Na; Ge, Di; Chen, Yihua
Abstract : Histone deacetylases (HDACs) are clinically validated epigenetic drug targets for cancer treatment. Abstract : Histone deacetylases (HDACs) are clinically validated epigenetic drug targets for cancer treatment. HDACs inhibitors (HDACis) have been successfully applied against a series of cancers. First-generation inhibitors are mainly pan-HDACis that target multiple isoforms which might lead to serious side effects. At present, the next-generation HDACis are mainly focused on being class- or isoform-selective which can provide improved risk–benefit profiles compared to non-selective inhibitors. Because of the rapid development in next-generation HDACis, it is necessary to have an updated and state-of-the-art overview. Here, we summarize the strategies and achievements of the selective HDACis.